Amoxicillin plus clavulanic acid in the treatment of recurrent urinary tract infections. - Brumfitt, W (1984)
Forty-four patients (43 female, 1 male), all with a history of recurrent urinary tract infections, were treated with 250 mg of amoxicillin plus 125 mg of clavulanic acid (one tablet of Augmentin) every 8 h for 7 days. The microbiological cure rates were 84% 1 week after the end of treatment and 67% 1 month later. Side effects, which were reported by 20% of the patients, were mild and in no case caused interruption of treatment. In view of the increasing trend in resistance to agents commonly used for the treatment of urinary tract infections in outpatients, the combination of amoxicillin and clavulanic acid may now be considered a first-line drug in patients with recurrent urinary tract infections.